Kaskadna nekakovost geodetskih podatkov - Radovan, Dalibor (Geodetski vestnik, 2011)
The geodetic profession provides geodetic data obtained in the fields of fundamental geodetic system, real estate and topography. Users integrate this data with other spatial data. The quality of such applications depends on the data quality; however, the providers and the users are not sufficiently aware of the cascading transfer of errors from the primary data layers to the secondary, derived data. Geodesy has traditionally considered errors mainly aspositional errors, according to the law of the transfer of errors. Since theera of widespread digitizing of geodetic data began in the 1990s, data quality in the realm of geographic information systems has been expressed withthe standardized parameters of data quality, and with metadata, of which positional accuracy is just one type. Unfortunately, in this way, the knowledge about which data is a reference can be obscured. To many users, it is not clear what is the specified quality referred to. This article describes, and intentionally uses, the term ćcascadingć, since for the rise ofdata quality one needs to upgrade data level by data level, starting first with the reference data and the semantic definitions of object types, and continuing by updating and harmonizing the secondary data, which were developed from the primary level. The reasons for the change of paradigm regarding the treatment of quality are considered. As the cascading poor quality of geodetic data can become a serious threat for the reputation of theprofession of geodesy, several contemporary applications and projects are described in which this has already happened. In the conclusion, proposals aregiven for improving the situationio
Keywords: cascading errors; hierarchy; hierarhija; kakovost geodetskega podatka; kaskadni prenos napak; reference data; referenčni podatek; spatial data quality